2013
DOI: 10.1371/journal.pone.0081844
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation Potentials of Human Umbilical Cord Mesenchymal Stem Cells Both Spontaneously and via 3-Methycholanthrene Induction

Abstract: Human umbilical cord mesenchymal stem cells (HUMSCs) are highly proliferative and can be induced to differentiate into advanced derivatives of all three germ layers. Thus, HUMSCs are considered to be a promising source for cell-targeted therapies and tissue engineering. However there are reports on spontaneous transformation of mesenchymal stem cells (MSCs) derived from human bone marrows. The capacity for HUMSCs to undergo malignant transform spontaneously or via induction by chemical carcinogens is presently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
1
35
0
2
Order By: Relevance
“…Therefore, they can be cellular vectors for delivering MMkilling agents. In fact, beyond their intrinsic tumor tropism [57], these cells possess further advantages for cytotherapies such as their virtually unlimited availability, low immunogenicity [58], anti-inflammatory potential [59], absence of spontaneous malignant transformation [60], and suitability to genetic manipulation [61]. However, further studies are needed to optimize their therapeutic use in preclinical models of MM as well as to define their efficacy and safety profiles for future cell-based gene therapies for the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they can be cellular vectors for delivering MMkilling agents. In fact, beyond their intrinsic tumor tropism [57], these cells possess further advantages for cytotherapies such as their virtually unlimited availability, low immunogenicity [58], anti-inflammatory potential [59], absence of spontaneous malignant transformation [60], and suitability to genetic manipulation [61]. However, further studies are needed to optimize their therapeutic use in preclinical models of MM as well as to define their efficacy and safety profiles for future cell-based gene therapies for the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the stability of human ASCs during prolonged cultivation with a low risk of tumorigenicity up to passage 20 . Although rare, spontaneous tumorigenic transformation of MSCs that are expanded in vitro has been reported, particularly when they were treated with certain carcinogens . For example, supplementing FGF2 in the culture medium of human bone marrow‐derived MSCs transfected with TERT (telomerase reverse transcriptase) resulted in an increased potential for neoplastic transformation .…”
Section: Introductionmentioning
confidence: 99%
“…10,20 Although rare, spontaneous tumorigenic transformation of MSCs that are expanded in vitro has been reported, particularly when they were treated with certain carcinogens. 21,22 For example, supplementing FGF2 in the culture medium of human bone marrow-derived MSCs transfected with TERT (telomerase reverse transcriptase) resulted in an increased potential for neoplastic transformation. 23 Thus, cell therapy with FGF2-treated ASCs may harbor a risk of tumorigenicity, especially after long-term stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…As HUMSCs are obtained from discarded umbilical cord tissue during caesarean sections, there are fewer ethical issues involved compared with ESCs. Compared with MSCs derived from adipose and bone marrow, HUMSCs represent a source of more primitive stromal cells that do not undergo spontaneous malignant transformation (9). Together with their relative ease of accessibility, cost-effectiveness, and efficacy, it is predicted that HUMSCs will have increasing application in tissue engineering and cellular-based therapies (10).…”
Section: Introductionmentioning
confidence: 99%